Polypoid Intratracheal Neurofibroma in a 58-Year-Old Man With No History of Von Recklinghausen Neurofibromatosis: A Case Report and Review of the Literature. (21st September 2018) - Shih, Jonathan; Nwanze, Julum; Daroca, Philip; Wang, Alun; Crawford, Byron; Nakanishi, Yukihiro
Abstract: In the chest cavity, neurofibromas are often seen in the posterior mediastinum, and multiple neurofibromas are often associated with von Recklinghausen neurofibromatosis. Endotracheobronchial neurofibromas are rare, and polypoid intratracheal neurofibromas are extremely rare. A 58-year-old man with a medical history of recently diagnosed clear cell renal cell carcinoma (8.8 × 7.0 × 5.5 cm on computed tomography) with a metastasis to the left femur (cT3aN1M1) presented with shortness of breath for several days. No history of von Recklinghausen neurofibromatosis was found in his medical history. Physical examination was notable for harsh tracheal sounds. Computed tomography of the chest showed a mid-tracheal polypoid lesion obstructing 80% to 90% of the airway. The patient underwent rigid bronchoscopy, which revealed a polypoid mass in the mid-trachea; the mass was removed with ablation and debulking with near-complete opening of the airway. Microscopic examination of the resected endotracheal polypoid mass demonstrated a diffuse proliferation of wavy spindle-shaped tumor cells with ovoid or elongated nuclei and variably collagenized matrix. The cellularity was low, and no mitotic figures were found. The mass showed a papillomatous architecture covered with respiratory-type epithelium. The spindle tumor cells were diffusely positive for vimentin and S100 and negative for smooth muscle actin, muscle-specific actin, neurofilament, and pan-cytokeratin. The Ki-67 index was less than 2%. The morphology and immunoprofile of the polypoid mass were consistent with the diagnosis of polypoid intratracheal neurofibroma. We hereby present an extremely rare case of intratracheal polypoid neurofibroma successfully treated with rigid bronchoscopy.